Eksistensi Yurisdiksi Tahta Suci Vatikan Terhadap Pelecehan Seksual Yang Dilakukan Oleh Pastor (Studi Kasus : 1997 Anak Di Illinois AS Jadi Korban Pelecehan Pastor) - Vika Nur Senda; Susi Sopiani (Universitas Kuningan, 2024)
The existence of the Holy See as a subject of international law has long been recognized and plays an important role in global dynamics. With its capacity as a subject of international law, the Holy See has equal rights and obligations with other states. The participation of the Holy See in The Convention on the Rights of the Child has the consequence that the Holy See has the same obligations as other countries that ratify this convention. Even though he is firm about its existence, the facts on the ground are still very contradictory. Because, although the Holy See has limited jurisdiction outside the Vatican area. Sexual abuse by priests in the Roman Catholic Church has become a highly sensitive and controversial issue in recent years. In essence, to maintain human dignity, human rights must be upheld and defended by all people, the law, the state and the government. This research was conducted using a descriptive-analytical method with a normative juridical approach. The results of the discussion of this article focus on how the Holy See of the Vatican uses its status as a subject of international law to influence global policies relatedto human rights and how the authority's rights to the services of the Catholic Church can be applied effectively in handling cases related to the Convention on the Rights of the Child